Testing the Effect of Variation of Deflector Shapes on the Performance of the Three Blade Vertical Axis Savonius Water Turbine - Gunawan, Gad; Susilo, Rizky Dwi; Kurniawati, Diniar Mungil (Politeknik Negeri Semarang, 2022)
Hydropower is energy obtained from flowingwater and can be used for mechanical energy or electricalenergy. Electrical energy is energy that is used to fulfill humanneeds in life. The need for electrical energy in Indonesiacontinues to increase by an average of 3.9% from year to yearuntil 2050. There are various water sources in Kalimantansuch as water ditches, as well as reservoirs that have low-speedwater flow and the capacity to accommodate water levels thatare not too high. The Savonius water turbine can be utilized inthese conditions because it has the advantage of a simpleturbine construction, and is suitable for relatively low velocitywater flows. This study analyzes how well the Savonius waterturbine is by applying different deflector shapes. The methodapplied in this experiment is an experimental study using aSavonius turbine. The conclusion in this study is that applyinga deflector will improve turbine performance much better thannot using a deflector. Experiments by applying deflectors,namely convex deflectors, flat deflectors, and concavedeflectors, it was concluded that the application using aconcave deflector resulted in the highest rotational speedproduced by the turbine, the maximum value of turbine powerand the Savonius turbine coefficient of 206.3 rpm, 0.196 Wattand Cp = 0.124.